Sociological Literary Analysis of the Short Story "Si Cantik yang Tak Boleh Keluar Malam" by Eka Kurniawan - Rizkia, Muhamad Fajar (Sebatik, 2025)
This research examines one of Eka Kurniawan's short stories titled “Si Cantik yang Tak Boleh Keluar Malam” using a sociological literary analysis approach. The method used in this research is descriptive qualitative with data collection through literature study. This approach is used to examine and understand the extent to which the short story depicts social, cultural, and societal issues occurring in the present community. The aim of this research is to understand the sociological perspective of literature in the short story and relate it to the current life and viewpoints of society. The literary sociology analysis conducted includes the social and cultural background, characters and social interactions, as well as the social characteristic structures present in the short story. The character of Si Cantik depicts a teenage girl who feels constrained and not free because she is not allowed to go out at night and cannot interact like her friends do. This becomes a common depiction in society when parents try to protect their children from undesirable things. This is done to protect and is evidence of parents trying to safeguard their children, which sometimes meets with resistance. This shows that there is a difference in social perspective between a child and their parents. Moreover, this is relevant to today's life when a child seems to want to be free without any constraints or limitations, whether from their parents or from the social environment in society.